The Ethnography of Surrogate Speech in a Foreign Language: The Case of the Timpani Drum Language among the Dagomba of Ghana - Hudu, F.A. (Journal of African Cultural Studies, 2023)
This article presents a study of the timpani drum beats and the akarima drummer among the Dagomba of Ghana, using analysis of audio and video recordings of drumming sessions and interviews with the drummers. Borrowed from the Asantes in the eighteenth century, the timpani transmits limited, oft-repeated messages in Akan, a language that neither the drummer nor his Dagomba patrons understand. In spite of this, the timpani is an integral part of Dagomba culture and rituals. In addition to transmitting messages, with the drum, the akarima guards tradition and culture heritage, and reinforces Dagomba values and cultural ethos. As a guardian of tradition, the akarima resists innovation of the practices associated with the use of the drum. As a constructor of realities, he creates knowledge and values from the praises of chiefs and imparts them to his patrons and actively moulds their lives to conform to these values. The article argues that, far from being a deficiency, the use of the drum to transmit messages in a language not comprehensible to the people contributes significantly to the success of the akarima, who functions as imparter of values to his listeners
Research Article
Keywords: Drum language; oral literature; surrogate